You are on page 1of 13

Chapter 14 Limits and Derivatives 31

CHAPTER 14 5. lim (2 x 2 − 3 x ) = 2(3)2 − 3(3)


x →3
=9
bñÉêÅáëÉ=NQ^=EéKRUF
6. lim (3 x 3 − 2 x 2 + 4 x − 5)
1. Let r cm be the radius of the circle. x →−1
2 πr = x = 3( −1)3 − 2( −1)2 + 4( −1) − 5
x = −14
r=

x x2 x+2 (1) + 2 3
y = πr = π( )2 =
2
7. lim 2 = =
2π 4π x →1 x + 3 (1) 2 + 3 4

2. f ( x ) = 2 x 2 − 3 x + 1 x2 − 9 ( x + 3)( x − 3)
8. lim = lim
(a) f (1) = 2(1)2 − 3(1) + 1 x →3 x − 3 x →3 x −3
=0 = lim ( x + 3)
x →3
(b) f ( −2) = 2( −2)2 − 3( −2) + 1 = (3) + 3
= 15 =6

(c) f ( k + 1) = 2( k + 1)2 − 3( k + 1) + 1
x3 − 8 ( x − 2)( x 2 + 2 x + 4)
= 2 k + 4 k + 2 − 3k − 3 + 1
2 9. lim = lim
x→2 x − 2 x→2 x−2
= 2k 2 + k = lim ( x 2 + 2 x + 4)
x→2
(d) f ( k − 1) = 2( k − 1)2 − 3( k − 1) + 1
= ( 2 ) + 2( 2 ) + 4
2
= 2 k 2 − 4 k + 2 − 3k + 3 + 1 = 12
= 2 k 2 − 7k + 6
x 2 − x − 12 ( x − 4)( x + 3)
10. lim = lim
3. g( x ) = x + 7 x − 8 x → 4 ( x + 4)( x − 4)
2
x → 4 x 2 − 16
(a) g( 4) = ( 4)2 + 7( 4) − 8 x +3
= lim
= 36 x→4 x + 4
( 4) + 3
(b) g( −2) = ( −2)2 + 7( −2) − 8 =
( 4) + 4
= −18 7
=
(c) g( a + 1) = ( a + 1)2 + 7( a + 1) − 8 8
= a 2 + 2 a + 1 + 7a + 7 − 8
x+2 x+2
= a 2 + 9a 11. lim = lim
x →−2 x + 8 x →−2 ( x + 2)( x 2 − 2 x + 4)
3
(d) g( a) − g( a − 1) 1
= lim 2
= a 2 + 7a − 8 − [( a − 1)2 + 7( a − 1) − 8] x →−2 x − 2 x + 4
= a 2 + 7a − 8 − a 2 + 2 a − 1 − 7a + 7 + 8 1
=
= 2a + 6 ( −2) − 2( −2) + 4
2

1
=
4. (a) f (1) = −5 12
k (1) + (1) − 12 = −5
2

k − 11 = −5 x 2 + 3x + 2 ( x + 1)( x + 2)
12. lim = lim
k=6 x →−1 x 2 + 5 x + 4 x →−1 ( x + 1)( x + 4)
x+2
(b) f ( x) = 0 = lim
x →−1 x + 4
6 x + x − 12 = 0
2
( −1) + 2
(2 x + 3)(3 x − 4) = 0 =
( −1) + 4
3 4
x=− or =
1
2 3 3
32 Chapter 14 Limits and Derivatives

x−3 17. (a) The graph of y = f ( x ) is drawn as follows.


13. lim y
x →3 x − 9 2

x−3 2
y = f (x) = x + x − 2
= lim 4
x →3 ( x+ 3)( x − 3)
1 3
= lim
x → 3 ( x + 3) x − 3 2 y = f (x) = −2x + 6
+ 1
Q When x → 3 , increases 1
( x + 3) x − 3
1
boundlessly; when x → 3− ,
x
is −3 −2 −1 O 1 2 3
( x + 3) x − 3
−1
not a real number.
−2
x−3
∴ lim does not exist.
x →3 x −9
2
(b) lim− f ( x ) = lim− ( x 2 + x − 2)
x →2 x →2
= (2) 2 + (2) − 2
1+ x −1 =4
14. lim
x→0 x lim+ f ( x ) = lim+ ( −2 x + 6) = −2(2) + 6 = 2
1+ x −1 1+ x +1 x→2 x→2
= lim
x→0 x 1+ x +1 ∴ The limit of f ( x ) at x = 2 does not exist.
1
= lim
x→0 1 + x + 1
1 18. (a) The graph of y = f ( x ) is drawn as follows.
= y
1 + (0) + 1
1
= 5
2
4 y = f (x)

3
( x + h )3 − x 3
15. lim
h→ 0 h 2
x + 3 x 2 h + 3 xh 2 + h 3 − x 3
3
= lim 1
h→ 0 h
x
= lim (3 x 2 + 3 xh + h 2 ) −4 −3 −2 −1 O 1 2 3 4
h→ 0
−1
= 3 x + 3 x (0) + (0)2
2
−2
= 3x 2
−3

−4
x+h − x
16. lim
h→ 0 h
x+h − x x+h + x (b) lim − f ( x ) = lim − ( − x 2 − 6 x − 5)
= lim x →−1 x →−1
h→ 0 h x+h + x
1 = −( −1)2 − 6( −1) − 5
= lim =0
h→ 0 x + h + x
1 lim f ( x ) = lim + ( x 2 − 2 x − 3)
= x →−1+ x →−1
x + (0) + x
= ( −1)2 − 2( −1) − 3
1
= =0
2 x
lim − f ( x ) = lim + f ( x )
x →−1 x →−1
=0
∴ The limit of f ( x ) at x = −1 exists.
Chapter 14 Limits and Derivatives 33

bñÉêÅáëÉ=NQ_=EéKSPF 2x + 3 2+ 3
2
7. lim = lim x =
1 − cos x 1 − cos x 1 + cos x x →∞ 3 x + 4 x →∞ 3 + 4 3
1. lim = lim x
x → 0 3x 2 x → 0 3x 2 1 + cos x
1 − cos 2 x
= lim 2 x−2
1 − 2
x → 0 3 x (1 + cos x ) 8. lim 2 = lim
x x2 = 0 − 0 = 0
x →−∞ x + 5 x x →−∞ 1 + 5 1+ 0
sin 2 x x
= lim 2
x → 0 3 x (1 + cos x )
1 sin 2 x 1 4 x 2 + 5x + 3 4+ 5 + 3
= lim lim 9. lim = lim
x x2
3 x→0 x 2 x → 0 1 + cos x x →∞ 3 x + 5 x + 8
2 x →∞ 3 + 5 + 8
x x2
1 1
= ( ) 4+0+0
3 2 =
1 3+0+0
= 4
6 =
3

2. lim
sin 4 x
= lim
4 x sin 4 x 5 x
x2 + 1 1+ 1
= lim x2
x → 0 sin 5 x x → 0 5 x 4 x sin 5 x 10. lim
4 sin 4 x 1 x →−∞ 1 − 5 x − 4 x 2 x →∞ 1 − 5 −4
x
x2
= lim
5 4 x → 0 4 x lim sin5 x5 x 1+ 0
5x →0
=
0−0−4
4
= =−
1
5 4

tan x 1 2 + 3x + 12
3. lim = lim =1 2 x 2 + 3x + 1
x→0 sin x x → 0 cos x 11. lim = lim 1 1 x
x →∞ x +1 x →∞
x
+ 2
x
2+ 3
x
+ 1
x Q When x → ∞ , the value of x2
1 x sin 2x
4. lim ( sin ) = lim 2 1
x
+ 1
x→0 x 2 x→0 x x x2
2 increases boundlessly.
1 sin 2x ∴ The limit does not exist.
= lim x
2 2x → 0 2
1 cos ax − cos bx
= 12. lim
2 x→0 x2
1 ax + bx ax − bx
= lim 2 [ −2 sin( )sin( )]
sin 2 2 x (2 x )(2 x ) sin 2 x 2 3 x x→0 x 2 2
5. lim = lim ( ) a +b )x
x → 0 x sin 3 x x → 0 x (3 x ) 2x sin 3 x 1 sin( a+b
= −2 lim 2 a + b2 ( )x
4 sin 2 x 2 1 x→0 x ( 2 )x 2
= lim ( )
3 2 x→0 2 x lim sin3 x3 x sin( a −2 b ) x a − b
3x → 0
( )x
=
4 ( a −2 b ) x 2
3
1 2 sin( a +2 b ) x
= (b − a 2 ) lim
2 ( a +2 b ) x → 0 ( a + b ) x
tan x sin x cos 2 x 2
6. lim = lim sin( a −2 b ) x
x→0 tan 2 x x → 0 cos x sin 2 x lim
= lim
x sin x 2 x cos 2 x ( a −2 b ) x → 0 ( a −2 b ) x
x → 0 2 x x sin 2 x cos x 1 2
1 sin x 1 cos 2 x = (b − a 2 )
= lim lim 2
2 x → 0 x lim sin2 x2 x x → 0 cos x
2 x→0

=
1 3x + 4 3 3+ 4 3+0 3 27
2 13. lim ( ) = lim ( 5 x )3 = ( ) =−
x →∞ 5 − 2x x →∞
x
−2 0 − 2 8
34 Chapter 14 Limits and Derivatives

2 −1 x
(b) ∆y = f ( x 0 + ∆x ) − f ( x 0 )
2 x − 2−x 2−x
14. lim x = lim = f (2.01) − f (2)
x →−∞ 2 + 2 − x
x
x →−∞ 2− x + 1
2 = 2(2.01) − (2.01)3 − [2(2) − (2)3 ]
2 −1 2x = −0.100 601
= lim
x →−∞ 2 2 x + 1 (c) ∆y = f ( x 0 + ∆x ) − f ( x 0 )
0 −1 = f (1.98) − f (2)
=
0 +1 = 2(1.98) − (1.98)3 − [2(2) − (2)3 ]
= −1
= 0.197 608

1 2. (a) ∆y = f ( x + ∆x ) − f ( x ) = 3 − 3 = 0
15. lim
x →∞ x 2 + 3x − x (b) ∆y = f ( x + ∆x ) − f ( x )
1 x + 3x + x
2 = [5 − 3( x + ∆x )2 ] − (5 − 3 x 2 )
= lim
x →∞ x 2 + 3x − x x 2 + 3x + x = 5 − 3 x 2 − 6 x∆x − 3( ∆x )2 − 5 + 3 x 2
x 2 + 3x + x = −6 x∆x − 3( ∆x )2
= lim 2
x →∞ x + 3 x − x 2 (c) ∆y = f ( x + ∆x ) − f ( x )
x 2 +3x +1 x + ∆x x
x2 = −
= lim x + ∆x + 2 x + 2
x →∞ 3 x 2 + 2 x + x∆x + 2 ∆x − x 2 − x∆x − 2 x
1 + 3x + 1 =
( x + ∆x + 2)( x + 2)
= lim
x →∞ 3 2 ∆x
=
1+ 0 +1 ( x + 2)( x + ∆x + 2)
=
3
2 dy ∆y
= 3. = lim
3 dx ∆x → 0 ∆x
[ 4( x + ∆x ) − 3] − ( 4 x − 3)
= lim
∆x → 0 ∆x
16. lim [ x ( x + 1 − x )] = lim 4
x →∞ ∆x → 0
[ x ( x + 1 − x )][ x ( x + 1 + x )] =4
= lim
x →∞ [ x ( x + 1 + x )]
x( x + 1 − x ) dy ∆y
= lim
4. = lim
x →∞ x ( x + 1 + x )
dx ∆x → 0 ∆x
1 3( x + ∆x )2 − 3 x 2
= lim = lim
x →∞ ∆x → 0 ∆x
x
2 ( x +1 + x)
x 3 x 2 + 6 x∆x + 3∆x 2 − 3 x 2
1 = lim
= lim ∆x → 0 ∆x
x →∞ 1+ 1 +1 = lim (6 x + 3∆x )
x ∆x → 0
=
1 = 6 x + 3(0)
1+ 0 +1 = 6x
1
=
2 dy ∆y
5. = lim
dx ∆x → 0 ∆x
[ −2( x + ∆x )2 + 4] − ( −2 x 2 + 4)
= lim
∆x → 0 ∆x
bñÉêÅáëÉ=NQ`=EéKSUF
−2 x 2 − 4 x∆x − 2( ∆x )2 + 4 + 2 x 2 − 4
1. (a) ∆y = f ( x 0 + ∆x ) − f ( x 0 ) = lim
∆x → 0 ∆x
= f (2.1) − f (2) = lim ( −4 x − 2 ∆x )
∆x → 0
= 2(2.1) − (2.1)3 − [2(2) − (2)3 ] = −4 x − 2(0)
= −1.061 = −4 x
Chapter 14 Limits and Derivatives 35

dy ∆y dy ∆y
6. = lim 9. = lim
dx ∆x → 0 ∆x dx ∆x → 0 ∆x
= lim {[2( x + ∆x )2 − 3( x + ∆x )
1
x + ∆x −1
− 1
x −1
∆x → 0 = lim
∆x → 0 ∆x
+ 4 − (2 x 2 − 3 x + 4)] ÷ ∆x} x − 1 − ( x + ∆x − 1)
= lim
= lim {[2 x 2 + 4 x∆x + 2( ∆x )2 − 3 x − 3∆x ∆x → 0 ∆x ( x − 1)( x + ∆x − 1)
∆x → 0
−1
+ 4 − 2 x 2 + 3 x − 4] ÷ ∆x} = lim
∆x → 0 ( x − 1)( x + ∆x − 1)
= lim ( 4 x + 2 ∆x − 3)
∆x → 0 −1
=
= 4 x + 2( 0 ) − 3 ( x − 1)( x + 0 − 1)
= 4x − 3
= −( x − 1) −2

dy ∆y dy ∆y
7. (a) = lim 10. = lim
dx ∆x → 0 ∆x dx ∆x → 0 ∆x
1 1
x + ∆x + 3
− 1
x +3
1 − 2 = lim
( x + ∆x ) 2 x ∆x → 0 ∆x
= lim
∆x → 0 ∆x x + 3 − ( x + ∆x + 3)
= lim
x − ( x + ∆x )2 ∆x → 0 ∆x ( x + 3)( x + ∆x + 3)
2
= lim −1
∆x → 0 ( ∆x ) x 2 ( x + ∆x ) 2 = lim
∆x → 0 ( x + 3)( x + ∆x + 3)
−2 x∆x − ( ∆x )2
= lim −1
∆x → 0 ( ∆x ) x 2 ( x + ∆x ) 2 =
( x + 3)( x + 0 + 3)
−2 x − ∆x
= lim 2 = −( x + 3) −2
∆x → 0 x ( x + ∆x ) 2
−2 x
= 2
x ( x + 0)2 dy ∆y
11. = lim
2 dx ∆x → 0 ∆x
=− 3
x
1 − 1
( x + ∆x ) 3 x3
= lim
∆x → 0 ∆x
dy −2 x 3 − ( x + ∆x )3
(b) = which is undefined. = lim 3
dx x = 0 0 ∆x → 0 x ∆x ( x + ∆x )3
∴ The slope of the tangent of y = f(x) at −3 x 2 − 3 x∆x − ( ∆x )2
= lim
x = 0 is undefined. ∆x → 0 x 3 ( x + ∆x )3
−3 x 2 − 3 x (0) − (0)2
=
x 3 ( x + 0 )3
dy ∆y
8. (a) = lim = −3 x −4
dx ∆x → 0 ∆x
( x + ∆x )3 − x 3
= lim ∆y
∆x → 0 ∆x 12.
dy
= lim
3 x 2 ∆x + 3 x ( ∆x )2 + ( ∆x )3 dx ∆x → 0 ∆x
= lim 2( x + ∆x ) −1 2 x −1
∆x → 0 ∆x 2( x + ∆x ) +1
− 2 x +1
= lim
= lim [3 x 2 + 3 x∆x + ( ∆x )2 ] ∆x → 0 ∆x
∆x → 0 = lim {{[2( x + ∆x ) − 1](2 x + 1)
= 3 x + 3 x (0) + (0)2
2 ∆x → 0
− [2( x + ∆x ) + 1](2 x − 1)}
= 3x 2
÷ {∆x[2( x + ∆x ) + 1](2 x + 1)}}
4 ∆x
(b)
dy
= 3(0)2 = lim
dx ∆x → 0 ∆x[2( x + ∆x ) + 1](2 x + 1)
x =0
=0 = 4(2 x + 1) −2
36 Chapter 14 Limits and Derivatives

dy ∆y = lim {{[ 1 + 2( x + ∆x ) − 1 + 2 x ]
13. = lim ∆x → 0
dx ∆x → 0 ∆x
2( x + ∆x ) + 3
− 2 x +3 [ 1 + 2( x + ∆x ) + 1 + 2 x ]}
3( x + ∆x ) − 2 3x − 2
= lim ÷ {∆x[ 1 + 2( x + ∆x ) + 1 + 2 x ]}}
∆x → 0 ∆x
= lim {{[2( x + ∆x ) + 3](3 x − 2) 1 + 2( x + ∆x ) − (1 + 2 x )
= lim
∆x → 0 ∆x → 0 ∆x[ 1 + 2( x + ∆x ) + 1 + 2 x ]
− (2 x + 3)[3( x + ∆x ) − 2]} 2
÷ {∆x (3 x − 2)[3( x + ∆x ) − 2]}} = lim
∆x → 0 1 + 2( x + ∆x ) + 1 + 2 x
−13∆x
= lim 2
∆x → 0 ∆x (3 x − 2 )[3( x + ∆x ) − 2] =
−13 1 + 2( x + 0 ) + 1 + 2 x
= lim
= (1 + 2 x ) − 2
1
∆x → 0 (3 x − 2 )[3( x + ∆x ) − 2]
−13
=
(3 x − 2)[3( x + 0) − 2]
dy ∆y
= −13(3 x − 2) −2 17. = lim
dx ∆x → 0 ∆x
4 − 4
x + ∆x x
dy ∆y = lim
14. = lim ∆x → 0 ∆x
dx ∆x → 0 ∆x 4 x − 4 x + ∆x
x + ∆x − 1−x x = lim
1− ( x + ∆x ) ∆x → 0 ∆x x x + ∆x
= lim
∆x → 0 ∆x ( 4 x − 4 x + ∆x )( 4 x + 4 x + ∆x )
(1 − x )( x + ∆x ) − x[1 − ( x + ∆x )] = lim
= lim ∆x → 0 ∆x x x + ∆x ( 4 x + 4 x + ∆x )
∆x → 0 ∆x (1 − x )[1 − ( x + ∆x )] 16 x − 16( x + ∆x )
∆x = lim
= lim ∆x → 0 ∆x x x + ∆x ( 4 x + 4 x + ∆x )
∆x → 0 ∆x (1 − x )[1 − ( x + ∆x )] −16
1 = lim
= lim ∆x → 0 x x + ∆x ( 4 x + 4 x + ∆x )
∆x → 0 (1 − x )[1 − ( x + ∆x )] −16
1 =
= x x + 0 (4 x + 4 x + 0 )
(1 − x )[1 − ( x + 0)]
= −2 x − 2
3

= (1 − x ) −2

dy ∆y
dy ∆y 18. = lim
15. = lim dx ∆x → 0 ∆x
dx ∆x → 0 ∆x 1 − 1
2 x + ∆x − 2 x = lim
3 + 4( x + ∆x ) 3+ 4 x
= lim
∆x → 0 ∆x ∆x → 0 ∆x
(2 x + ∆x − 2 x )(2 x + ∆x + 2 x ) 3 + 4 x − 3 + 4( x + ∆x )
= lim = lim
∆x → 0 ∆x (2 x + ∆x + 2 x ) ∆x → 0 ∆x 3 + 4 x 3 + 4( x + ∆x )
4( x + ∆x ) − 4 x = lim {{[ 3 + 4 x − 3 + 4( x + ∆x )][ 3 + 4 x
= lim ∆x → 0
∆x → 0 ∆x (2 x + ∆x + 2 x )
4 + 3 + 4( x + ∆x )]} ÷ {∆x 3 + 4 x
= lim
∆x → 0 2 x + ∆x + 2 x 3 + 4( x + ∆x )[ 3 + 4 x + 3 + 4( x + ∆x )]}}
4 = lim {[3 + 4 x − (3 + 4 x + 4 ∆x )] ÷{∆x 3 + 4 x
= ∆x → 0
2 x+0 +2 x
3 + 4( x + ∆x )[ 3 + 4 x + 3 + 4( x + ∆x )]}}
= x−
1
2

= lim {−4 ÷ { 3 + 4 x 3 + 4( x + ∆x )[ 3 + 4 x
∆x → 0
+ 3 + 4( x + ∆x )]}}
dy ∆y
16. = lim = −4 ÷ { 3 + 4 x 3 + 4( x + 0)[ 3 + 4 x
dx ∆x → 0 ∆x
1 + 2( x + ∆x ) − 1 + 2 x + 3 + 4( x + 0)]}
= lim
= −2(3 + 4 x ) − 2
3
∆x → 0 ∆x
Chapter 14 Limits and Derivatives 37

dy ∆y 2. f ( x ) = x 2 − 3 , g( x ) = 3 x − 4
19. = lim
dx ∆x → 0 ∆x
x + ∆x (a) f ( −1) + g( −1) = ( −1)2 − 3 + 3( −1) − 4 = −9
− x
x + ∆x + 2 x +2
= lim (b) f ( k + 1) − g( k − 1)
∆x → 0 ∆x
x + 2 ( x + ∆x ) − x x + ∆x + 2 = ( k + 1)2 − 3 − [3( k − 1) − 4]
= lim = k 2 + 2 k + 1 − 3 − 3k + 3 + 4
∆x → 0 ∆x x + 2 x + ∆x + 2
= lim {{[ x + 2 ( x + ∆x ) − x x + ∆x + 2 ] = k2 − k + 5
∆x → 0
[ x + 2 ( x + ∆x ) + x x + ∆x + 2}
÷ {∆x x + 2 x + ∆x + 2 3. f ( x ) = 2 x 2 + 5 x − 7
[ x + 2 ( x + ∆x ) + x x + ∆x + 2 ]}} (a) f ( −2) = 2( −2)2 + 5( −2) − 7 = −9
= lim {[( x + 2)( x + ∆x )2 − x 2 ( x + ∆x + 2)]
∆x → 0 (b) f ( 4) = 2( 4)2 + 5( 4) − 7 = 45
÷ {∆x x + 2 x + ∆x + 2 [ x + 2 ( x + ∆x ) (c) f ( x 2 ) = 2( x 2 )2 + 5( x 2 ) − 7 = 2 x 4 + 5 x 2 − 7
+ x x + ∆x + 2 ]}}
= lim {( x 2 + 4 x + x∆x + 2 ∆x ) (d) [ f ( x )]2 = (2 x 2 + 5 x − 7)2
∆x → 0 = 4 x 4 + 10 x 3 − 14 x 2 + 10 x 3 + 25 x 2
÷ { x + 2 x + ∆x + 2
− 35 x − 14 x 2 − 35 x + 49
[ x + 2 ( x + ∆x ) + x x + ∆x + 2 ]}}
= 4 x 4 + 20 x 3 − 3 x 2 − 70 x + 49
= {x + 4 x + x (0) + 2(0)} ÷ { x + 2
2

x + (0) + 2 [ x + 2 ( x + 0) + x x + 0 + 2 ]}
1 4. lim (3 x 3 − 7 x 2 + 4 x − 8)
= ( x + 4)( x + 2) − 2
3
x→2
2
= 3(2)3 − 7(2)2 + 4(2) − 8
= 24 − 28 + 8 − 8
dy ∆y = −4
20. = lim
dx ∆x → 0 ∆x
2( x + ∆x ) − 1
2( x + ∆x )
− (2 x − 1 )
= lim
2x (2 x + 1)2 [2(0) + 1]2 1
∆x → 0 ∆x 5. lim = = =1
x → 0 ( x + 1)3 (0 + 1)3 1
2 ∆x + − x + x + ∆x
2 x ( x + ∆x )
= lim
∆x → 0 ∆x
x−2 x−2
1 6. lim = lim
= lim [2 + ] x→2 x→2 ( x + 2)( x − 2)
∆x → 0 2 x ( x + ∆x ) x −4
2

1 x−2
=2+ = lim
2 x ( x + 0) x→2 x+2
1 =0
=2+ 2
2x
sin 2 x sin 3 x 3 sin 2 x 4x
7. lim = lim lim
21 − 22. No solutions are provided for the H.K.C.E.E. x → 0 sin 4 x sin 7 x 14 x → 0 2 x x → 0 sin 4 x
questions because of the copyright reasons. sin 3 x 7x
lim lim
x → 0 3 x x → 0 sin 7 x
3
=
oÉîáëáçå=bñÉêÅáëÉ=NQ=EéKTMF 14

1. f ( x ) = x 2 − 4 x − 5 sin 2 3 x
8. lim
(a) f ( −2) = ( −2)2 − 4( −2) − 5 = 7 x → 0 x sin 4 x
9 sin 3 x sin 3 x 4x
(b) f ( k − 2) = ( k − 2)2 − 4( k − 2) − 5 = lim lim lim
4 x → 0 3 x x → 0 3 x x → 0 sin 4 x
= k 2 − 4k + 4 − 4k + 8 − 5 9
=
= k 2 − 8k + 7 4
38 Chapter 14 Limits and Derivatives

cos 5 x − cos 3 x −2 sin 4 x sin x dy ∆y


9. lim = lim = lim
x→0 x 2 x→0 x2 dx ∆x → 0 ∆x
sin 4 x sin x 1 3 3
= −8 lim lim = lim [2 − −2+ ]
x→0 4 x x→0 x ∆x → 0 ∆x x + ∆x x
= −8 3 x + ∆x − x
= lim
∆x → 0 ∆x x ( x + ∆x )

1 − 4x = 3 x −2
x2 − 4x
10. lim = lim
x →∞ 3 x 2 + x x →∞ 3 + 1
x dy ∆y
1 16. = lim
= dx ∆x → 0 ∆x
3 1 1 1
= lim [ x + ∆x − −x+ ]
∆x → 0 ∆x x + ∆x x
3− x + 2
5 6 1 x + ∆x − x
3x 2 − 5x + 6 = lim [ ∆x + ]
11. lim = lim 2 5 x ∆x → 0 ∆x x ( x + ∆x )
x →∞ 2x + 5 x →∞
x
+ 2 1
x
3− 5 + 6 = lim [1 + ]
x x2 ∆x → 0 x ( x + ∆x )
Q When x → ∞ , the value of
+ = 1 + x −2
2 5
x x2
increases boundlessly.
∴ The limit does not exist. dy ∆y
17. = lim
dx ∆x → 0 ∆x
1 1 1
dy ∆y = lim [2( x + ∆x ) + − 2x − 2 ]
12. = lim ∆x → 0 ∆x ( x + ∆x ) 2
x
dx ∆x → 0 ∆x
2( x + ∆x ) + 7 − 2 x − 7 1 x 2 − ( x + ∆x )2
= lim = lim [2 ∆x + 2 ]
∆x → 0 ∆x x ( x + ∆x )2
∆x → 0 ∆x
= lim 2 1 ( x − x − ∆x )( x + x + ∆x )
∆x → 0
= lim [2 ∆x + ]
∆x → 0 ∆x x 2 ( x + ∆x )2
=2
2 x + ∆x
= lim [2 − 2 ]
∆x → 0 x ( x + ∆x )2
dy ∆y
13. = lim 2x
dx ∆x → 0 ∆x =2− 4
x
= lim {[( x + ∆x )2 − 2( x + ∆x ) − 3 − x 2 2
∆x → 0 =2− 3
+ 2 x + 3] ÷ ∆x} x
∆x (2 x + ∆x − 2)
= lim
∆x → 0 ∆x x + ∆x + 1 x + 1
= lim (2 x + ∆x − 2)
18. (a) −
x + ∆x + 4 x + 4
∆x → 0
x + ∆x + 4 − 3 x + 4 − 3
= 2x − 2 = −
x + ∆x + 4 x+4
3 3
dy ∆y = 1− −1+
14. = lim x + ∆x + 4 x+4
dx ∆x → 0 ∆x x + ∆x + 4 − x − 4
1 1 1 = 3[ ]
= lim [ − ] ( x + 4)( x + ∆x + 4)
∆x → 0 ∆x 2( x + ∆x ) − 5 2 x − 5 3∆x
1 2 x − 5 − 2 x − 2 ∆x + 5 =
= lim ( x + 4)( x + ∆x + 4)
∆x → 0 ∆x (2 x + 2 ∆x − 5)(2 x − 5)
−2 d x +1 1 x + ∆x + 1 x + 1
= lim (b) ( ) = lim ( − )
∆x → 0 (2 x + 2 ∆x − 5)(2 x − 5) dx x + 4 ∆x → 0 ∆x x + ∆x + 4 x + 4
= −2(2 x − 5) −2 1 3∆x
= lim
∆x → 0 ∆x ( x + 4)( x + ∆x + 4)
3
2x − 3 3 = lim
15. y = =2− ∆x → 0 ( x + 4)( x + ∆x + 4)
x x = 3( x + 4) −2
Chapter 14 Limits and Derivatives 39

19. No solution is provided for the H.K.C.E.E. question sin 3 x − 3 sin x


because of the copyright reasons. 25. lim
x→0 x3
sin(2 x + x ) − 3 sin x
= lim
20. Let the function f ( x ) = ax 2 + bx + c . x→0 x3
Q f ( x ) − f ( x − 1) = 4 x sin 2 x cos x + sin x cos 2 x − 3 sin x
= lim
x→0 x3
∴ ax 2 + bx + c − a( x − 1)2 − b( x − 1) − c = 4 x
2 ax + b − a = 4 x 2 sin x cos 2 x + sin x − 2 sin 3 x − 3 sin x
= lim
2 a = 4 gives a = 2 x→0 x3
b − a = 0 b = 2 2 sin x − 2 sin 3 x + sin x − 2 sin 3 x − 3 sin x
  = lim
∴ f ( x) = 2 x 2 + 2 x + c x→0 x3
f (1) = 2 + 2 + c = 4 −4 sin 3 x
= lim
c =0 x→0 x3
sin x 3
∴ The function is f ( x ) = 2 x 2 + 2 x . = −4 lim ( )
x→0 x
= −4
21. Let f ( x ) = ax 2 + bx + c .
Q f ( x ) + f ( x + 2) = 2 x 2 − 10 x
4x − 3 3 4 − 3x 3
∴ ax + bx + c + a( x + 2) + b( x + 2) + c = 2 x − 10 x
2 2 2 26. lim ( ) = lim ( )
x →∞ 5x + 1 x →∞ 5 + 1
x
2 ax 2 + ( 4 a + 2 b) x + 4 a + 2 b + 2c = 2 x 2 − 10 x 4
= ( )3
f (0) = 0 + 0 + c = 5 5
64
2 a = 2 =
4 a + 2 b = −10 125
4 a + 2 b + 2 c = 0

c = 5
∴ a = 1 , b = −7 , c = 5 x2 + 2 − x2 + 1
27. lim
∴ The function is f ( x ) = x 2 − 7 x + 5. x →∞ x
x2 + 2 x2 + 1
= lim ( − )
x −2 x −2
x →∞ x2 x2
22. lim = lim 2 1
x→4 x−4 x → 4 ( x − 2 )( x + 2 ) = lim ( 1 + 2 − 1 + 2 )
1 x →∞ x x
= lim = 1−1
x→4 x + 2
1 =0
=
4
dy ∆y
28. = lim
dx ∆x → 0 ∆x
4+x −2 ( 4 + x − 2)( 4 + x + 2)
23. lim = lim 4 − ( x + ∆x )2 − 4 − x 2
x→0 x x→0 x ( 4 + x + 2) = lim
4+x−4 ∆x → 0 ∆x
= lim 4 − ( x + ∆x )2 − 4 + x 2
x → 0 x ( 4 + x + 2) = lim
1 ∆x → 0 ∆x ( 4 − ( x + ∆x )2 + 4 − x 2 )
=
4 −(2 x + ∆x )
= lim
∆x → 0 4 − ( x + ∆x )2 + 4 − x 2
3 sin θ − sin 2θ 3 sin θ sin 2θ −2 x
24. lim = lim ( − ) =
θ→ 0 2θ θ → 0 2θ 2θ 2 4 − x2
3 sin θ sin 2θ
= lim − lim = − x(4 − x 2 )− 2
1

2 θ→ 0 θ 2 θ → 0 2θ
1
=
2
40 Chapter 14 Limits and Derivatives

dy ∆y (n − 1)!(n + 1)!
29. = lim = lim
dx ∆x → 0 ∆x n →∞ 2(n!)2
1 x + ∆x x n +1
= lim [ − ] = lim
∆x → 0 ∆x x + ∆x + 1 x +1 n →∞ 2 n
= lim {[( x + ∆x ) x + 1 − x x + ∆x + 1 ] 1 1
= lim ( + )
∆x → 0
n →∞ 2 2 n
÷ [ ∆x ( x + ∆x + 1)( x + 1)]} 1
=
= lim {[( x + ∆x )2 ( x + 1) − x 2 ( x + ∆x + 1)] 2
∆x → 0
÷ {∆x ( x + ∆x + 1)( x + 1)[( x + ∆x ) 1 1 1
(b) lim (1 + )(1 + )(1 + )
n →∞ 1× 3 2×4 3×5
x + 1 + x x + ∆x + 1 ]}} 1
= lim {[ x 2 + 2 x + ∆x ( x + 1)] L[1 + ]
∆x → 0
n( n + 2 )
= lim {{(1 × 3 + 1)(2 × 4 + 1)(3 × 5 + 1)
÷ { ( x + ∆x + 1)( x + 1)[( x + ∆x ) x + 1 n →∞
+ x x + ∆x + 1 ]}} L[n(n + 2) + 1]} ÷ [(1 × 3)(2 × 4)(3 × 5)
x ( x + 2) L (n)(n + 2)]}
= 3
2 x ( x + 1) 2 2[2 2 ⋅ 32 ⋅ 4 2 L (n + 1)2 ]
= lim
1 n →∞ (n!)(n + 2)!
= ( x + 2)( x + 1) − 2
3

2 2[(n + 1)!]2
= lim
n →∞ ( n!)( n + 2 )!
2(n + 1)
båêáÅÜãÉåí=NQ=EéKTOF = lim
n →∞ n + 2
n2 + n + 1 n2 + n + 1 2 + 2n
1. (a) lim = lim
n →∞ 1 + 2 + L + n n →∞ 1 ( n 2 + n) = lim
2 n →∞ 1 + 2
n
n2 + n + 1 =2
= 2 lim
n →∞ n 2 + n
1 + 1n + 12 1 A B
= 2 lim n 3. (a) ≡ +
n →∞ 1 + 1
n
k ( k + 1) k k + 1
=2 1 ≡ A( k + 1) + Bk
3 + 9 + 27 + L + 3n Put k = −1, B = −1
(b) lim
n →∞ 3n + 1 Put k = 0 , A = 1
3(3 − 1) 1
n ∴ A = 1, B = −1
= lim
n →∞ 3 − 1 3n + 1 n
∑1+ 2 +L+ k
(b) Sn = 1
3 3n − 1
= lim n k =1
2 n →∞ 3 + 1 n
1 − 3− n ∑ 12 k(k + 1)
1
3
= lim =
2 n →∞ 1 + 3− n k =1
3 n
=
∑ k(k + 1)
2
2 =
k =1
1 1 1 n
2. (a) lim (1 − 2 )(1 − 2 )L(1 − 2 )
∑ k(k + 1)
1
n→∞ 2 3 n =2
k =1
= lim [(2 2 − 1)(32 − 1)( 4 2 − 1)L(n 2 − 1) n
n→∞
∑ [ k − k + 1]
1 1
=2
÷ (2 ⋅ 32 ⋅ 4 2 L n 2 )]
2

= lim [(2 − 1)(2 + 1)(3 − 1)(3 + 1)( 4 − 1)( 4 + 1) k =1


n→∞ 1
= 2(1 − )
L(n − 1)(n + 1) ÷ (2 ⋅ 3 ⋅ 4 L n )]
2 2 2 2 n +1
1 1
= lim {[(2 − 1)(3 − 1)L(n − 1)] [(0 + 1)(1 + 1) ∴ lim Sn = lim 2(1 − )=2
n→∞ 2 n →∞ n →∞ n +1
(2 + 1)(3 + 1)L(n + 1)] ÷ (1 ⋅ 2 ⋅ 3 L n 2 )}
2 2 2
Chapter 14 Limits and Derivatives 41

4. (a) Let P(n) be the proposition `ä~ëëïçêâ=N=EéKROF


x x x sin x
cos cos 2 L cos n = n . 1. (a) 4 x + 3 y = 420
2 2 2 2 sin( xn ) 420 − 4 x
2
x y=
When n = 1 , L.H.S. = cos 3
2
sin x (b) A = 2( xy)
R.H.S. = 420 − 4 x
2 sin 2x = (2 x )( )
3
2 sin 2x cos 2x
= 840 x − 8 x 2
2 sin 2x =
3
x
= cos
2 (c) When x = 21 ,
∴ P(1) is true. 840(21) − 8(21)3
the enclosed area = [ ] m2
Assume P(k) is true for any positive integer k, 3
x x x sin x = 4 704 m 2
i.e. cos cos 2 L cos k = k .
2 2 2 2 sin( xk ) (d) When the enclosed area = 3 000 m 2 ,
2

Then cos
x x x x
cos 2 L cos k cos k +1 840 x − 8 x 2
2 3 000 =
2 2 2 3
sin x cos kx+1 1125 = 105 x − x 2
= 2
2 k sin( xk ) x 2 − 105 x + 1125 = 0
2
2 sin x cos kx+1 105 ± 1052 − 4(1 125)
= 2
x=
2 k +1 sin( xk ) 2
2
x 105 ± 15 29
sin x 2 cos 2 k +1 =
= k +1 2
2 sin 2( kx+1 )
2
sin x 2 cos kx+1
= k +1 2
2. f ( x ) = 3 x 2 − 2 x − 5
2 2 cos kx+1 sin kx+1
2 2
sin x (a) f (1) = 3(1)2 − 2(1) − 5
= k +1 = −4
2 sin( kx+11 )
2
(b) f ( −2) = 3( −2)2 − 2( −2) − 5
Thus assuming P(k) is true for any positive = 11
integer k, P(k + 1) is also true. By the principle
of mathematical induction, P(n) is true for (c) f ( a + 2) = 3( a + 2)2 − 2( a + 2) − 5
all positive integers n.
= 3a 2 + 12 a + 12 − 2 a − 4 − 5
(b) lim cos
x x x
cos 2 L cos n = 3a 2 + 10 a + 3
n →∞ 2 2 2
sin x (d) f ( k − 1) = 3( k − 1)2 − 2( k − 1) − 5
= lim n
n →∞ 2 sin( xn ) = 3k 2 − 6k + 3 − 2 k + 2 − 5
2
x = 3k 2 − 8k
sin x 2 n
= lim (e) f ( −1) − f (1) = 3( −1)2 − 2( −1) − 5 − ( −4)
n →∞ x sin( xn )
2 =4
x
sin x 2n
= lim lim (f) f ( p + 1) − f ( p − 1)
n →∞ x n →∞ sin( xn )
2 = 3( p + 1)2 − 2( p + 1) − 5 − (3 p 2 − 8 p)
sin x
= = 3 p2 + 6 p + 3 − 2 p − 2 − 5 − 3 p2 + 8 p
x = 12 p − 4
42 Chapter 14 Limits and Derivatives

`ä~ëëïçêâ=O=EéKRSF 3x 3 x
2. lim = lim
x → 0 2 sin x 2 x → 0 sin x
1. lim ( x 2 + 1) = ( −1)2 + 1 = 2 3 1
x →−1 =
2 lim sinx x
x→0
3 x + 1 3(3) + 1 3
2. lim = = 10 =
x →3 x − 2 (3) − 2 2

( x + 2)( x − 1)( x − 3)
3. lim tan 2 x 1 sin 2 x
x →−2 4x2 + 9x + 2 3. lim = lim
x→0 x x → 0 x cos 2 x
( x + 2)( x − 1)( x − 3)
= lim = lim
2 x sin 2 x 1
x →−2 ( x + 2)( 4 x + 1)
x→0 x 2 x cos 2 x
( x − 1)( x − 3)
= lim = 2 lim
sin 2 x
lim
1
x →−2 4x + 1 2 x → 0 2 x 2 x → 0 cos 2 x
[( −2) − 1][( −2) − 3] =2
=
4( −2) + 1
15
=− sin θ
7 4. lim = lim cos θ = 1
θ→ 0 tan θ θ → 0
x3 + 1 ( x + 1)( x 2 − x + 1)
4. lim = lim
x →−1 x + 1 x →−1 x +1 2θ 2 θ θ
5. lim = 2 lim
= lim ( x 2 − x + 1) θ → 0 sin 2 θ θ → 0 sin θ sin θ
x →−1
1 1
= ( −1)2 − ( −1) + 1 =2
lim θ lim sinθ θ
sin θ
=3 θ→ 0 θ→ 0
=2
2( x + h ) 2 − 2 x 2
5. lim
h→ 0 h
1 − cos 2 x 2 sin 2 x
2 x 2 + 4 xh + 2 h 2 − 2 x 2 6. lim = lim
= lim x→0 x2 x→0 x2
h→ 0 h sin x sin x
= lim ( 4 x + 2 h) = 2 lim lim
h→ 0 x→0 x x→0 x
= 4 x + 2( 0 ) =2
= 4x

x −1 x −1 x+3 +2
6. lim = lim `ä~ëëïçêâ=Q=EéKSOF
x →1 x + 3 − 2 x →1 x + 3 − 2 x + 3 + 2
( x − 1)( x + 3 + 2) 4 x 2 + 3x + 1 4+ x + 2 3 1
= lim 1. lim = lim x
x →1 x +3− 4 x →∞ 2x + 1
2 x →∞ 2 + 12
x
= lim ( x + 3 + 2) 4+0+0
x →1 =
= 1+ 3 + 2 2+0
=2
=4

(2 x + 1)3 8 x 3 + 12 x 2 + 6 x + 1
2. lim = lim
`ä~ëëïçêâ=P=EéKSMF x →∞ x 3 − 1 x →∞ x3 − 1
sin mx sin mx 8 + x + 62 + 13
12
1. lim = lim m = lim x x
x→0 x x→0 mx x →∞ 1 − 13
x
sin mx
= m lim 8+0+0+0
mx → 0 mx =
= m(1) 1− 0
=8
=m
Chapter 14 Limits and Derivatives 43

2.
3. lim ( x 2 − x − x ) y = f (x) f (x + ∆x) ∆y = f (x + ∆x) − f (x)
x →∞
( x 2 − x − x )( x 2 − x + x ) (a) y = 3x + 1 3x + 3∆x + 1 3∆x
= lim
x →∞ x2 − x + x (b) y = 2x − 5 2x + 2∆x − 5 2∆x
x − x − x2
2
= lim 2 2
x →∞ x2 − x + x (c) y = x 2− 2 x + 2x∆x + (∆x) − 2 ∆x (2x + ∆x )
−x −∆x
= lim (d) y=
1 1
x →∞ x+1 x + ∆x + 1 (x + ∆x + 1)(x + 1)
x −x +x
2
−1
= lim
x →∞ x2 −x +1
x2 `ä~ëëïçêâ=S=EéKSUF
−1 ∆y
= lim 1. f ' ( x ) = lim
x →∞ 1− 1 +1
x ∆x → 0 ∆x
−1 2( x + ∆x )2 − 2 x 2
= = lim
1− 0 +1 ∆x → 0 ∆x
=−
1 4 x∆x + 2( ∆x )2
= lim
2 ∆x → 0 ∆x
= lim ( 4 x + 2 ∆x )
∆x → 0
4. lim [ ( x + 1)( x + 2) − x ]
x →∞ = 4 x + 2( 0 )
[ ( x + 1)( x + 2) − x ][ ( x + 1)( x + 2) + x ] = 4x
= lim
x →∞ ( x + 1)( x + 2) + x
( x + 1)( x + 2) − x 2 dy ∆y
= lim 2. = lim
x →∞ ( x + 1)( x + 2) + x dx ∆x → 0 ∆x
3x + 2 2 x + ∆x − 2 x
= lim = lim
x →∞ ∆x → 0 ∆x
x 2 + 3x + 2 + x
(2 x + ∆x − 2 x )(2 x + ∆x + 2 x )
3 + 2x = lim
= lim ∆x → 0 ∆x (2 x + ∆x + 2 x )
x →∞ x 2 +3x + 2 + 1 4 x + 4 ∆x − 4 x
x2 = lim
∆x → 0 ∆x (2 x + ∆x + 2 x )
3 + 2x
= lim = lim
4
x →∞ 1 + 3x + 22 + 1 ∆x → 0 2 x + ∆x + 2 x
x
3+0 4
= =
1+ 0 + 0 +1 2 x+0 +2 x
1
=
3 =
2 x

`ä~ëëïçêâ=R=EéKSRF dy ∆y
3. = lim
1. (a) ∆y = f ( x 0 + ∆x ) − f ( x 0 ) dx ∆x → 0 ∆x
= f (1.1) − f (1)
1
x + ∆x
− 1
= lim x

=
1

1 ∆x → 0 ∆x
2(1.1) − 1 2(1) − 1 −1
= lim
= −0.17 (corr. to 2 d.p.) ∆x → 0 x ( x + ∆x )
−1
(b) ∆y = f ( x 0 + ∆x ) − f ( x 0 ) =
x ( x + 0)
= f (0.8) − f (1) 1
1 1 =− 2
= − x
2(0.8) − 1 2(1) − 1
= 0.67 (corr. to 2 d.p.)